Comment on “Adenosinergic regulation of the expansion and immunosuppressive activity of CD11b+Gr1+ cells” - Shevchenko, Ivan; Bazhin, Alexandr V.; Umansky, Viktor (Medical principles and practice, 2012)
In their recent article, Ryzhov et al. ([1][1]) reported that the granulocytic CD11b + Gr1high subset of myeloid-derived suppressor cells (MDSCs) generated from mouse hematopoietic progenitor cells in vitro displayed the highest levels of CD73 (ecto-5′-nucleotidase) expression followed by CD11b +